Film in the Spanish class: contrasting representations of Franco's Spain in El andén and ¡Bienvenido, Mr Marshall! - Ibarz, Toni; Ibarz, Alexander (Journal of Iberian & Latin American Studies, 2007)
The article proposes a teaching model developed to harness film's ability to communicate cultural descriptions and to maximize this ability using a comparative analytical classroom praxis which help students develop critical thinking and discursive abilities. The proposed model is a comparison of two Spanish films both made in 1952 which have opposing views of a particular issue: Luis García Berlanga's "Bienvenido, Mr Marshall!" and Eduardo Manzanos' "El andén."